Deuterium retention in recrystallized tungsten irradiated with simultaneous deuterium–neon ion beams. (August 2017) - Finlay, T.J.; Davis, J.W.; Schwarz-Selinger, T.; Siketić, Z.; Haasz, A.A.
Highlights: D retention in W measured for simultaneous D-Ne implantations at 300–700 K. D and Ne retention measured by thermal desorption spectroscopy (TDS) up to 1473 K. Depth profiles for D, He and Ne measured by NRA and ERDA. 1 keV Ne + reduces D retention in W by at least the same amount as 500 eV He + . TDS and depth profiles suggest differences in the D retention reduction mechanisms for Ne versus He. Abstract: Although neon has been considered for impurity seeding in the ITER tungsten divertor, there have been few studies on its effects on deuterium retention in tungsten. We investigate the effects of simultaneous (SIM) D-2.5% Ne ion beam irradiation on D retention in recrystallized W at 300–700 K, with 500 eV/D + and 1 keV/Ne + ion energies, and compare to the effects of SIM D-3% He irradiation with 500 eV/He + . Thermal desorption spectroscopy (TDS) up to 1473 K, nuclear reaction analysis (NRA), and elastic recoil detection analysis (ERDA) are used to measure D, He, and Ne in the specimens. Ne is more effective than He at reducing D retention for higher exposure temperatures, even though less Ne is retained than He. He appears to modify the D TDS spectra peak shapes more than Ne, while He addition leads to increased D trapping within a few µm depth according to NRA. D retention may be reduced due to Ne sputtering, as well as a near surface interaction with Ne which blocks D diffusion past the implantation range and leads to higher surface re-emission.